PELAKSANAAN PENDAFTARAN TANAH DALAM MEWUJUDKAN KEPASTIAN HUKUM HAK ATAS TANAH DI INDONESIA - Muh. Reza Zulfikar; Irma Maulani Batu Bara; Putri Ramadhani (Universitas 17 Agustus 1945 Samarinda, 2026)
Land registration is one of the key instruments in Indonesian agrarian law for providing legal certainty regarding land rights. Through land registration, rights holders obtain legal protection for their land ownership. However, in practice, various problems still arise, such as land disputes, overlapping certificates, a lack of public awareness regarding land registration, and weak land administration. This study aims to analyze the implementation of land registration in realizing legal certainty regarding land rights in Indonesia and to examine the obstacles encountered in its practical implementation. The research method used is normative legal research with a legislative approach and a conceptual approach. The results of the study indicate that land registration plays a crucial role in creating legal certainty, legal protection, and orderly land administration. However, its implementation still faces various obstacles from both the public and government bureaucracy. Therefore, strengthening the land administration system, increasing public legal awareness, and enforcing the law effectively are necessary to realize a fair and legally certain land system.